Carol Sawyer: The Natalie Brettschneider Archive, Vancouver Art Gallery - Wieland, Alexandra (Archivaria, 2018)
Carol Sawyer: The Natalie Brettschneider Archive. Vancouver Art Gallery, Vancouver, British Columbia 28 October 2017 – 4 February 2018. Curated by Bruce Grenville.